Predictors of cardiovascular disease in patients with chronic kidney disease VD stage treated with hemodialysis - I.M. Shifris; I.O. Dudar; Е.К. Krasiuk; А.Yu. Shymova (Medičnì Perspektivi, 2021)
The aim of the study was to establish the frequency and possible predictors of cardiovascular disease (CVD) in chronic kidney disease (CKD) VD stage patients, treated with hemodialysis, based on results of prospective observation. The prospective observational cohort study  included 223 patients with CKD V D stage who were treated with hemodialysis (HD) during 2012-2019. The research was carried out in two stages. At the first stage, main demographic, laboratory and clinical characteristics of patients, including the frequency of CVD, at the time of beginning the study were examined. At the second stage, based on prospective studying of the dynamics of the frequency of CV pathology, an assessment of potential predictors of CVD in CKD V D stage patients treated with HD was made. Patients’ characteristics determined at the beginning of the study were used as possible predictors. The average duration of prospective study was 35.5±17.8 months, cumulative – 579.3 patient-years. For determination of prognostic factors of CVD events, ROC-analysis, univariate and multivariate Cox proportional hazard regression analysis were done. The primary endpoint (newly diagnosed CVDs) was assesses at the end of the study.  Statistical processing of the obtained results was performed using the MedCalc Statistical Software, version 19.3. During the study period, a significant increase of all CVD frequency by 80% (р<0.001) was stated, more than twice – of coronary artery disease (CAD; р<0.001) and atrial fibrillation (AF; р=0.0039). The incidence rate of CVD and CAD was 9.8 and 9.15 per 100-patient-years, respectively. The primary endpoint was observed in 92 (41.26%) patients: newly diagnosed CAD – in 53 patients, heart failure – in 12 patients, AF – in 9 patients, acute myocardial infarction – in 8 patients, other heart diseases – in 10 patients. Independent predictors on increased CVD risk in chronic kidney disease VD stage patients treated with hemodialysis are: age over 35 years, use of a central venous catheter as a vascular access during HD initiation, history of nasal MRSA collonization. In the other hand, serum albumin level of more than 36,6 g/l was associated with reduced risk.